Development of the anterior pituitary: diverse lineages of the stem/progenitor cells - Yukio Kato; Takako Kato (Endocrine Journal)
The pituitary gland is endocrine tissue composed of two distinct parts with different origins: the adenohypophysis (adenohypophyseal placode origin) and the neurohypophysis (neuroectoderm origin). Differentiation of endocrine cells in the pituitary gland leads to hormone synthesis, secretion into the capillary network, and transportation to target organs. In 1988, the discovery of the pituitary transcription factor PIT1 sparked research on endocrine cell differentiation. In the twenty-first century, the discovery that SOX2-positive stem/progenitor cells give rise to all types of pituitary endocrine cells advanced research on differentiation processes using diverse marker molecules. Lineage tracing using specific marker genes from early embryos revealed that during construction of the anterior pituitary from the adenohypophyseal placodal cells the developing anterior pituitary incorporates diverse cell types originating from the neural crest-derived and ectodermal-derived cells. Consequently, the postnatal anterior pituitary becomes a mosaic of terminally differentiated cells of different origin and with different life histories. It has also been revealed that most of the postnatal stem/progenitor cells form at least solid clusters in the parenchyma. Moreover, the classification and role of S100β-positive cells had been ambiguous, but now they are identified as a major component of postnatal stem/progenitor cells. This paper provides an updated overview of pituitary development.